Pernikahan Beda Agama pada Pemberitaan di Portal Berita Online (Studi pada Detik.com, Republika.co dan Kompas.com) - Hilmiyah, Mifda Hilmiyah; Masyhur, Zulkarnaim; Arif, Farida M.; Fitriana, A.Dian (LPPM IAIN Parepare, 2024)
Abstract: This research aims to examine news about interfaith marriages on Indonesian news portals. The issue of interfaith marriage is sensitive in Indonesia because it is related to religion, culture, and social society. This research uses Entman framing analysis. This analysis is divided into four concepts, namely defining the problem, factors causing the problem, moral decisions, and problem-solving. Detik.com carries out externalization by adapting to sociocultural conditions where Indonesia's diverse society requires diverse information. Detik.com does not consider religious ideology as a basis for reporting. Republika.co media to be intersubjective to institutionalize approval for the legalization of interfaith marriages with constitutional legitimacy. Republika.co describes itself as a media that represents Muslim groups. Internalization of Kompas.com is guided by its vision to respect the diversity and diversity of Indonesian society. Kompas.com tends to be tolerant and raise minority issues. Keywords: framing, interfaith marriage, news portal